Calcium and iron nanoparticles: A positive modulator of innate immune responses in strawberry against Botrytis cinerea. (April 2022) - Mogazy, Asmaa M.; Mohamed, Heba I.; El-Mahdy, Omima M.
Abstract: Botrytis cinerea is considered one of the most important diseases, causing significant loss of strawberry fruits both before and after harvest. The current study sought to assess the green biosynthesis of calcium and iron nanoparticles from thyme plants as an alternative method to controlling strawberry preharvest diseases. Different concentrations of green synthesized calcium and iron nanoparticles (100 and 200 ppm) were foliar sprayed individually or in combination against B. cinerea. The treatments decreased the growth of B. cinerea. When compared to infected plants, treatment with 200 ppm calcium and iron individually or in combination resulted in a significant reduction in the disease incidence of gray mold. Furthermore, treatment with 200 ppm calcium and iron resulted in significant increases in vitamin content (E, C, A), peroxidase, β-1, 3-glucanase, phenylalanine ammonia lyase cell wall fractions (lignin, cellulose, pectin, hemicellulose), mineral content (Ca 2+, Fe, N, P, K +, Mg 2+ and Zn 2+ ), phenolics, and flavonoids when compared to infected plants. As a result, high concentrations of calcium and iron nanoparticles, individually or in combination, may achieve an acceptable level of disease control while also inducing plant resistance against pathogens. Graphical Abstract: ga1 Highlights: Calcium and iron nanoparticles were green synthesized from thyme plant. Calcium and iron nanoparticles have antifungal activity against B. cinerea . Gray mold disease may be controlled by using calcium and iron nanoparticles. Calcium and iron nanoparticles activate defense enzymes, phenolic and flavonoids compounds.